1986
DOI: 10.1111/j.1365-2621.1986.tb13853.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective Molecular Weight of Aqueous Solutions and Liquid Foods Calculated From the Freezing Point Depression

Abstract: Freezing point depression (FPD) methods were applied to estimate the effective molecular weights of pure solutions and liquid foods. Explicit expressions among FPD, molecular weight and concentration were developed. The estimated molecular weights were about 333-356 for skim milk, 347-3.50 for coffee beverage, 164-167 for grape juice and 196-203 for tomato juice. The FPD methods were considered accurate for nonacidic foods but they could underestimate the values for acidic foods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 4 publications
1
41
0
1
Order By: Relevance
“…The negative value of B indicates that a fraction of solids is behaving as a solvent. Chen [35] indicated that melting/freezing point depression results from the complex interaction between solutes and water and can be expressed by equivalent increases in free water. Thus, the values of B can either be positive or negative depending on the behavior of food constituents.…”
Section: Sugarsmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative value of B indicates that a fraction of solids is behaving as a solvent. Chen [35] indicated that melting/freezing point depression results from the complex interaction between solutes and water and can be expressed by equivalent increases in free water. Thus, the values of B can either be positive or negative depending on the behavior of food constituents.…”
Section: Sugarsmentioning
confidence: 99%
“…The Clausius-Clapeyron equation is applicable to ideal systems, but multicomponent systems are normally nonideal in nature. The Chen equation [35] is an extension of the Clausius-Clapeyron equation and may be used to predict the freezing temperature for non-ideal systems. The Chen equation (6) is expressed as:…”
Section: Characterizing the Effects Of Solids Content On Equilibrium mentioning
confidence: 99%
“…Con base en la concentración relativa de los azúcares presentes en el jugo, se calculó el peso molecular efectivo del jugo de uchuva, aplicando la ecuación 3 propuesta por Chen et al (1986):…”
Section: Determinación Experimental Y Predicción Del Punto De Congelaunclassified
“…Several investigations on the A T in food systems have been carried out from the following standpoints: the freezing point and ice fraction of glucose and sucrose in the high concentration range (Pongsawatmanit & Miyawaki, 1993), the relationship between A T and solute composition (sugars and organic acids) in fruit juice systems (Chen et al, 1990), the effective molecular weight of aqueous solutions and liquid foods calculated from AT (Chen, 1986), the AfT of aqueous saccharide solution (sucrose, fructose, Iactose, etc.) and liquid foods (Lerici et al, 1983), the equation ofnon-ideal AfT of a sucrose solution (Fullerton et al, 1992), the equation of the relationship between A T and molal concentration in low ( lO%:~) sucrose concentration (Prentice,1 978), determination of the mean molecular mass of carbowax polyols by AT (Huszur & Pasztor, 1986), the empirical equation for the relationship between A T and concentration (Chen & Nagy, 1987), application of the approximate A T equation of bound water theory to characterize the equilibrium freezing curve (Schwartzberg, 1976;Chen, 1988), and calculation of the coefficient of solute-solvent interaction by the equation for the relationship between Af T and concentration in glycerol solution (Chen, 1987).…”
mentioning
confidence: 99%